Упростите:а)(2x+y)(y-2x)б)(c+3d)^2Разложите ** множители:a-3b+9b^2-a^2Решите...

0 голосов
70 просмотров

Упростите:
а)(2x+y)(y-2x)
б)(c+3d)^2
Разложите на множители:
a-3b+9b^2-a^2
Решите уравнение:
-(3x-4)^2=28-(3x+2)(3x-2)


Алгебра (31 баллов) | 70 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1. а) ( 2х+ у ) ( у - 2х ) = ( у + 2х ) ( у - 2х) = у^2 - 4х^2
б) ( с + 3d )^2 = c^2 + 6сd + 9d^2.

2. a - 3b + 9b^2 - a^2 = а - 3b + (3b)^2 - a^2 = a - 3b + ( 3b^2 - a ) ( 3b ^2 + a ) =
= ( a - 3b ) ( 1 - 3b^2 - a ).

3. -( 3х - 4 )^2 = 28 - ( 3х + 2 ) ( 3х - 2)
- ( 9х^2 - 24х + 16 ) = 28 - ( 9х^2 - 4 )
-9х^2 + 24х - 16 = 28 - 9х^2 + 4
-9х^2 + 24х + 9х^2 = 28 + 4 + 16
24х = 48
х = 48 : 24
х = 2.
Ответ : х = 2.
Удачи)))

(3.7k баллов)
0 голосов

Решите задачу:

1)(2x+y)(y-2x)=(y+2x)(y-2x)=y^2-4x^2 \\ (c+3d)^2=c^2+6cd+9d^2 \\ \\ 2)a-3b+9b^2-a^2=(a-3b)-(a^2-9b^2)=(a-3b)-(a-3b)(a+ \\ +3b)=(a-3b)(1-(a+3b))=(a-3b)(1-a-3b) \\ \\ 3)-(3x-4)^2=28-(3x+2)(3x-2) \\ -(9x^2-24x+16)=28-(9x^2-4) \\ -9x^2+24x-16=28-9x^2+4 \\ -9x^2+24x-16-28+9x^2-4=0 \\ 24x-48=0 \\ 24x=48 \\ x=2
(10.7k баллов)